2009
DOI: 10.1371/journal.pone.0007302
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Controlled Trial of RTS,S/AS02D and RTS,S/AS01E Malaria Candidate Vaccines Given According to Different Schedules in Ghanaian Children

Abstract: BackgroundThe target delivery channel of RTS,S candidate malaria vaccines in malaria-endemic countries in Africa is the World Health Organisation Expanded Program on Immunization. As an Adjuvant System, age de-escalation and schedule selection step, this study assessed 3 schedules of RTS,S/AS01E and RTS,S/AS02D in infants and young children 5–17 months of age in Ghana.MethodologyA Phase II, partially-blind randomized controlled study (blind to vaccine, not to schedule), of 19 months duration was conducted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 19 publications
8
60
2
Order By: Relevance
“…In addition, modest pain reduction was noted at the lower adjuvant dose compared to the full dose. Finally, clinical trial results showed reduced reactogenicity in children receiving a malaria vaccine containing AS01 (a liposome adjuvant system containing MPL and QS21) compared to the same vaccine containing AS02 (an emulsion adjuvant system containing MPL and QS21) (26). Taken together, the MF59 and AS series clinical trials demonstrate that reduction or removal of oil content has the potential to reduce local reactogenicity, although this effect may depend on each vaccine's composition and its intended recipients.…”
Section: Figmentioning
confidence: 96%
“…In addition, modest pain reduction was noted at the lower adjuvant dose compared to the full dose. Finally, clinical trial results showed reduced reactogenicity in children receiving a malaria vaccine containing AS01 (a liposome adjuvant system containing MPL and QS21) compared to the same vaccine containing AS02 (an emulsion adjuvant system containing MPL and QS21) (26). Taken together, the MF59 and AS series clinical trials demonstrate that reduction or removal of oil content has the potential to reduce local reactogenicity, although this effect may depend on each vaccine's composition and its intended recipients.…”
Section: Figmentioning
confidence: 96%
“…Fox et al compounds when combined with a recombinant malaria vaccine; 6 this vaccine is now in Phase III clinical trials in African children. We have developed an anionic liposomal formulation containing GLA (GLA-LS) and demonstrated protective immune responses in mice when combined with ID93, 7 although T helper type 1 immunogenicity markers were not induced to the same magnitude as with GLA-SE.…”
mentioning
confidence: 99%
“…Immunogenicity of the RTS,S vaccine is adjuvant dependent, and a formulation in alum, the aluminum adjuvant present in most licensed vaccines, elicited suboptimal protection against sporozoite challenge (10,11). The current RTS,S adjuvant formulation was derived empirically and is comprised of a mixture of monophosphoryl lipid A (MPL) and QS21, a purified fraction of the detergent saponin, in an oil-in-water emulsion (AS02) or a liposome (AS01) formulation (12,13).…”
mentioning
confidence: 99%